Interactome analysis of the EV71 5′ untranslated region in differentiated neuronal cells SH-SY5Y and regulatory role of FBP3 in viral replication - Huang, Hsing-I; Chang, Ying-Ying; Lin, Jhao-Yin; Kuo, Rei-Lin; Liu, Hao-Ping; Shih, Shin-Ru; Wu, Chih-Ching (Proteomics (Weinheim), 2016)
Enterovirus 71 (EV71), a single‐stranded RNA virus, is one of the most serious neurotropic pathogens in the Asia‐Pacific region. Through interactions with host proteins, the 5′ untranslated region (5′UTR) of EV71 is important for viral replication. To gain a protein profile that interact with the EV71 5′UTR in neuronal cells, we performed a biotinylated RNA‐protein pull‐down assay in conjunction with LC–MS/MS analysis. A total of 109 proteins were detected and subjected to Database for Annotation, Visualization and Integrated Discovery (DAVID) analyses. These proteins were found to be highly correlated with biological processes including RNA processing/splicing, epidermal cell differentiation, and protein folding. A protein–protein interaction network was constructed using the STRING online database to illustrate the interactions of those proteins that are mainly involved in RNA processing/splicing or protein folding. Moreover, we confirmed that the far‐upstream element binding protein 3 (FBP3) was able to bind to the EV71 5′UTR. The redistribution of FBP3 in subcellular compartments was observed after EV71 infection, and the decreased expression of FBP3 in host neuronal cells markedly inhibited viral replication. Our results reveal various host proteins that potentially interact with the EV71 5′UTR in neuronal cells, and we found that FBP3 could serve as a positive regulator in host cells.